NILAI BUDAYA DAN MENTALITAS MAHASISWA AKUNTANSI - Kartikawati Halim; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to understand culture and mentality value that accountant students have. This research uses qualitative method with phenomenological approach. Phenomenological approach is used to describe culture and mentality value that accountant students have while learning process occurs. This research uses primary data which is obtained through in-depth interview from informants that is Economic and Business Faculty of Diponegoro University’s accountant students and accountant students’ parents. Obtained data were analyzed based on the result of the interview.The result of this research shows that there are seven culture and mentality value that accountant students have, such as : discipline, self awareness, responsibility, mutual assistance, courtesy, independent, and honesty.